Effect of recombinant bovine Somatotropin (rbST) and propylene glycol (PG) on quantity and quality embryos in early lactation Brown Swiss dairy cows - Payano, Ide Unchupaico; Eulogio, Carlos Quispe; Gomez, Edith Ancco; Villar, Fernando Arauco; Cruz, Alex Huamán de la (Revista de Ciências Agroveterinárias, 2025)
This study aimed to evaluate the effects of recombinant bovine somatotropin (rbST) and propylene glycol (PG) on embryo production in early-lactating dairy cows. Thirty Brown Swiss cows were randomly assigned to three groups: control (n=10), PG (n=10), and rbST (n=10). All animals underwent a superovulation protocol. On Day 0, cows in the PG and rbST groups received 200 ml of PG (RUMINIL®, Montana) and 500 mg of rbST (BOOSTIN-S®, Battilana), respectively. Additionally, on Day 0, all cows were administered an intravaginal progesterone-releasing device (1200 mg DISPOCEL®, Von Franken), 1 mg of estradiol benzoate, and 40 mg of cloprostenol intramuscularly. On Day 4, they received 350 mg of FSH (Folltropin® - Vetoquinol). On Day 7, the device was removed, and 40 mg of cloprostenol was administered. On Day 9, artificial insemination was performed. On Day 16, embryos were collected and evaluated. ANOVA results indicated that cows in the PG group exhibited a higher number of recovered structures, recovered embryos, and unfertilized structures compared to the control and rbST groups. The rbST group showed the highest number of viable embryos (quality 1 and 2). The PG group also had the highest number of morulas and blastocysts, while the rbST group presented the highest number of early blastocysts. Additionally, rbST administration resulted in an increase of 19.3% and 18.3% of serum glucose concentrations (mg/dL) (p < 0.05) and milk production (p < 0.05), respectively compared to both the PG (16.7%, 12.5%) and control groups (10.6%, 3.4%). The inclusion of PG in the superovulation protocol enhanced the number of embryos, whereas rbST improved embryo quality and developmental stage.